Molecular docking studies of new thiazolidin‑4‑one derivatives as combretastatin A4 analogues - Makki, Sajjad; Al-Hussein, Baneen Abd; Al-Zahra, Safa Abd; Razak, Abeer; Obies, Mohammed; Balakit, Asim; Makki, Tuqa (Pharmakeftiki, 2025)
In the present study, a series of thiazolidin-4-one derivatives were designed as analogues of combretastatin A4 (CA4); a known anti-tubulin agent. The molecular structures incorporate either a 3,4,5-trisubstituted phenyl ring or a 3-alkoxy-4-methoxyphenyl ring, with the two aromatic systems connected via an amide linkage and a thiazolidin-4-one scaffold. Structural variation was introduced through different substituents (R groups) on the 4-methoxyphenyl ring. All compounds, along with CA4 as the reference molecule, were subjected to molecular docking studies targeting the tubulin β-2B chain (Protein Data Bank code: 8QEA). The docking results revealed that the newly synthesized molecules exhibit binding affinities and inhibition constant (Ki) values comparable to those of CA4. These findings suggest that the designed thiazolidin-4-one derivatives warrant further experimental investigation for their potential as anti-tubulin (i.e., anti-cancer) agents.